A paper-based microbial fuel cell array for rapid and high-throughput screening of electricity-producing bacteria. Issue 12 (21st June 2015) - Choi, Gihoon; Hassett, Daniel J.; Choi, Seokheun
<x xml:space="preserve">Abstract</x> In this work, a 48-well, paper-based sensing platform was developed for the high-throughput and rapid characterization of the electricity-producing capability of microbes.